Comparative Efficacy of Biological, Botanical and Chemical Treatments Against Damping Off Disease of Tomato in Chitwan - Sharma, Laxmi Kharel; Sharma, Nisha; Dhungana, Babita; Adhikari, Aakash; Shrestha, Sundar Man; Yadav, Dharmendra (International Journal of Social Sciences and Management, 2022)
A field experiment on “Comparative Efficacy of Biological, Botanical and Chemical Seed Treatments against Damping Off Disease of Tomato in Bhojad, Chitwan” was conducted from 1st October to 1st November 2020. The test was placed on Randomized Complete Block Design (RCBD) with five treatments and four responses. The treatments were included Trichoderma harzianium (107 cfu ml-1) as a bio control agent, Bavistin (2g/litre of water) as chemical treatments and Neem extract as botanical treatments. The germination percentage, pre, and post-emergence damping-off, plant height, root weight and shoot weight, dry root and dry shoot weight of tomato seedlings were recorded. There was a significant increment in germination percentage (86.25%), reduction in pre and post disease incidence (23% and 5.16%), highest plant height (41.20 cm), highest fresh root weight, and fresh shoot weight (0.9725g and 12.300g), highest dry root and dry shoot weight (0.1975g and 1.393g) respectively were found when the Bavistin treatment was given however Trichoderma harzianum (107 cfu ml-1) treatment was also found significantly effective for controlling damping-off of tomato as compared to control which is non-hazardous to environment and the human being so, is suggested to use for organic agriculture. Int. J. Soc. Sc. Manage. Vol. 9, Issue-2: 67-74.